DETERMINANT OF MAIZE FARMERS HOUSEHOLD FOOD SECURITY IN DRY LAND MADURA ISLAND, INDONESIA - Setiani, Setiani; Wijayanti, Dian Eswin; Priyanto, Moh. Wahyudi (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2025)
Food security must be ensured not only at the national and regional levels but also at the household level. The aims of this research were to examine the status and factors influencing food security among maize farmer households in the study area. A cross-sectional study was conducted between September and October 2023. A total of 151 households from two villages were chosen through a multi-stage sampling method. The household food security status was evaluated using the Household Dietary Diversity Score (HDDS). A binary logistic regression model was utilized to determine the factors influencing food security among maize farmer households. The study found that the majority (55%) of maize farmers experienced food insecurity, with an average HDDS of 7.23. The regression analysis indicated that household income, education level of the housewife, diversity of farm production, and cash transfers had a positive impact on food security.  The findings imply that improving household income, promoting education (especially for housewives), encouraging diversified farming practices, and providing cash transfers are effective measures to enhance food security among maize farmers. These implications can guide policymakers and development practitioners in designing interventions to address food insecurity in agricultural communities. Enhancing the nutritional knowledge of housewives and promoting the cultivation of a greater variety of food plants in home gardens are recommended to improve household food security.